Pre‐Existing Off‐Fault Damage Can Impede Coseismic On‐Fault Slip - C. H. Wu; P. Cui; Y. Klinger; X. B. Tan; S. J. Yi; Y. S. Li (Geophysical Research Letters)
Abstract Primarily due to the scarce direct field evidence along a same fault, understanding the relationship between the pre‐existing off‐fault damage and coseismic slip distribution remains challenging. This study offers the first field‐based quantitative assessments of fault damage zones along the surface rupture generated by the 2008 Mw 7.9 Wenchuan earthquake in China over eight profiles with 254 outcrops. The width and mean tectonic fracture intensity of the damage zones exhibit pronounced variations along the fault strike. We introduce the damage index as a proxy to quantify the extent of pre‐existing damage. We find a statistically significant anti‐correlation between the damage index and coseismic on‐fault slip. We thus infer that pre‐existing off‐fault damage plays a significant role in dissipating rupture energy, thereby reducing coseismic on‐fault slip. This study provides a natural case for linking the long‐term fault zone evolution and the short‐term earthquake rupture dynamics.